Phenomenology Of Material Within Artistic Practice - Md Arif, Mohd Fuad; Khairani, Mohd Zahuri (2016)

(untitled)
This paper will emulate the position of material within the compound of artistic practice, or refereed here within the practice of modern and contemporary art such as painting, sculpture, art installation. Objectively frame within a phenomenological perspective the discussion will show how domestically materials are understood and engage within and from an array of understandings that does not establish its location of it being just for the sake of usability or mean to an end, but that of dynamic and indebted to other entities which becomes an actor that institute meaning. As this is a conceptual paper the reading from such perspective will be interpretative where examples are taken and cross referred in connection towards the subject discuss. Such understanding is significant towards opening a way within the understanding itself that departs from a subscription that perceived material as being passive actor in the scheme of artistic practices. With such insight within this inquiry future set of engagement, be it conceptually or even practical, can be further develop by future art researchers or practitioners towards the question concerning material that goes beyond its mere usability understanding